An Insight into the Level of Information about Sustainability of Edible Insects in a Traditionally Non-Insect-Eating Country: Exploratory Study - Guiné, Raquel P. F. (2021)
Insects have been reported as a possible alternative solution to help feed the growing world pop-ulation with less stress on the planet, thus contributing to the preservation of the environment and natural ecosystems. However, the consumption of edible insects (EIs), although culturally ac-cepted for some communities, is not readily accepted for others. Hence this work explores the lev-el of information that people in a traditionally non-insect-eating country have about the sustaina-bility issues related with EIs, and also some possible reasons that could motivate their consump-tion. The study was based on a questionnaire survey and the results were explored by descriptive statistic tools, tree classification analysis, factor analysis and cluster analysis. The results showed that the level of information is still low in general, with most people not manifesting an opinion. However, some aspects are relatively familiar to the participants (88.9% know that the ecological footprint of insects is smaller than other meats and 86.9% know that they efficiently convert or-ganic matter into protein). Factor and cluster analysis showed three classes: cluster 1—people not informed about the facts disclosed through the true statements and also not able to distinguish the false information; cluster 2—people not informed about the facts disclosed through the true statements but who were able to distinguish the false information; and cluster 3—people well in-formed about the facts disclosed through the true statements but who were marginally unable to distinguish the false information. It was also found that education, sex and professional area are the most relevant sociodemographic factors associated with the level of information, and the highest motivations to consume EIs are their contribution to preserve the environment and natu-ral resources followed by being a more sustainable option (for 64.7% and 53.4% of participants, respectively). Hence it was concluded that, although some work still needs to be done to better inform people about EIs, there is already some conscientiousness that they constitute a good and more sustainable alternative to other types of meat.